Implementasi Program Peningkatan Edukasi di bidang Lingkungan Hidup - Romula Adiono; Hefry Johan Ferdhianzah; Daniar Rizky Rahmadiansyah (Jurnal Syntax Admiration, 2024)
The implementation of the Education Improvement Program in the field of Environment is a strategic effort to increase public awareness and knowledge about environmental issues. The program is designed to meet increasingly complex environmental challenges by providing an effective and sustainable education. This study evaluates the effectiveness of various environmental education methods, including seminars, workshops, and media campaigns. Through a data-based approach, the analysis was carried out to measure the impact of the program on changes in participants' attitudes and behaviors towards environmental issues. The results show that interactive and participatory methods are more successful in increasing community understanding and engagement. This finding is expected to be a reference for the development of better environmental education programs in the future.